THE CORRELATION BETWEEN EMOTIONAL ABUSE AND MENTAL HEALTH PROBLEMS IN MARRIED INDIVIDUALS - Poutiainen, Poutiainen .M; Holma, Holma J. (International Journal of Current Practice in Management and Leadership (IJCPML), 2022)
Emotional abuse has been identified as a pervasive problem that affects married individuals, often leading to adverse mental health outcomes. This quantitative correlational survey aimed to investigate the relationship between emotional abuse, mental health problems, and quality of life among 230 married individuals in Karachi, Pakistan. The study used the Gottman Emotional Abuse Questionnaire, Mental Health Inventory, and Quality of Life Scale for assessment. Data analysis was carried out using SPSS version-22. The results of the study showed that emotional abuse was a significant predictor of mental health problems and poor quality of life. The findings suggest that emotional abuse targets individuals with less power and influence, leading to long-lasting effects on their confidence and self-worth. Depression, anxiety, dissociation, alcohol and drug use, and social isolation were identified as some of the psychosocial consequences of emotional abuse. The study highlights the need for preventative interventions to address emotional abuse and maintain healthy relationships.